Art for animals : visual culture and animal advocacy, 1870-1914 - Cronin, J. Keri (Jennifer Keri), 1973- (Animalibus., 2018)
"Explores the ways in which visual imagery was used for animal advocacy campaigns in the late nineteenth and early twentieth centuries, and the ways in which these images were created, circulated, and consumed in a wide range of cultural contexts"--Provided by publisher.